"A good intention gone awry": Queering makerspaces to support queer creators. Issue 1 (18th October 2019) - Floegel, Diana
ABSTRACT: Although library makerspaces encourage community‐building and creativity, normative values in libraries may prevent queer individuals from using these spaces. Interviews with 11 adult queer entertainment media (EM) creators were analyzed using constructivist grounded theory to explore participants' perspectives on creating in libraries. Opportunities and obstacles related to physical spaces, community relationships, and resources demonstrate that makerspaces should be considered within overall contexts of library services in order to examine libraries' utility for queer people. Results support the idea that makerspaces need to be woven into library programs and services more broadly to make libraries more inclusive environments.